PROCESSING POSSIBILITIES OF BIRCH OUTER BARK INTO GREEN BIO-COMPOSITES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The main objective of the study was to obtain bio-composites from grey alder sawdust using a mixture of birch outer bark suberinic acids as a binder, and to test their mechanical properties. Ethanol-extracted birch outer bark was used as a raw material for the investigation. Characteristics (suberinic acids content, epoxy acids content and acid number) of the hydrolytically depolymerized birch outer bark binder were also determined. The initial filler/binder ratio and molding parameters (temperature and pressure) were established by the full factorial design. Preliminary data showed that the increase of the pressing temperature from 160 to 200 °C at a pressure of 3.5 MPa resulted in a minor growth of the boards’ density (up to 1.0 g/cm3) and bending strength (up to 17.1 MPa).Our investigation has shown that it is possible to use one of the plywood production residues – outer birch bark – as a raw material for obtaining particleboards, which have mechanical properties beyond the standard limits. The used method is also environmentally friendly, easy realizable in practice and has a potential to be cost-effective.